Some results on semi maximal filters in BL−algebras - Mahta Bedrood; Asiyeh Hassani Movahed; Arsham Borumand Saeid (Journal of Mahani Mathematical Research)
In this article, we present an equivalent definition for the concept of the semi maximal filter in $BL-$algebras and some of their properties are studied. At first, we focus on elucidating the relationship between semi maximal filters and minimal prime filters. By conducting this analysis, some classifications for semi maximal filters are given.